Terwilliger Algebras of Group Association Schemes of Matrix Groups - Nur Hamid ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2025)
This paper investigates the Terwilliger algebras ofsome group association schemes related to matrix groups. We obtainthe structure of the Terwilliger algebras for the general andthe special linear group of 2×2 matrices over the field of order5. In particular, we determine the Wedderburn decomposition ofthese algebras.